The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14042415
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technology and Services for Sustainable Agriculture in Tanzania: A Literature Review

Abstract: Digital technology has the potential to eradicate extreme poverty and food insecurity to the majority of smallholder farmers in the world. This paper aims to identify knowledge gaps on digital technology for sustainable agriculture and assess their availability to smallholder farmers worldwide. The particular case of Tanzania receives special attention. We conducted an extensive literature search from relevant databases for review. The advanced digital technology in agriculture, mostly used by large scale farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 55 publications
1
39
0
3
Order By: Relevance
“…The digital management information system with ERP as the typical representative is considered as one of the important foundations for the internal digital transformation of enterprises (Pizzi et al, 2021). Digital technology will also promote satellite communication enterprises to improve the production process with products and processes as the entry point and promote the digital transformation of manufacturing industry (Mushi et al, 2022;Wen et al, 2022). Therefore, management mode reform and production process improvement can effectively promote the formation of internal advantages of digital transformation of satellite communication enterprises.…”
Section: Research Modelmentioning
confidence: 99%
“…The digital management information system with ERP as the typical representative is considered as one of the important foundations for the internal digital transformation of enterprises (Pizzi et al, 2021). Digital technology will also promote satellite communication enterprises to improve the production process with products and processes as the entry point and promote the digital transformation of manufacturing industry (Mushi et al, 2022;Wen et al, 2022). Therefore, management mode reform and production process improvement can effectively promote the formation of internal advantages of digital transformation of satellite communication enterprises.…”
Section: Research Modelmentioning
confidence: 99%
“…Extensive irrigation makes use of 70% of the available freshwater resources. Internet of ings (IoT) and machine learning (ML)-based solution may help in efficient monitoring, controlling, and irrigation scheduling for agriculture fields [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have shown that rural digitalization has shaped various dynamic attitudes, behaviors, and abilities, though the opportunities for using digital technology are unchanged (Dewi et al, 2022). Rural entrepreneurship digitalization could alleviate extreme poverty and food insecurity for most small farmers worldwide (Sathya, 2019;Abeysinghe & Malik, 2021;Mushi et al, 2022). Studies have shown that rural digitalization technology could fill the void of new institutional theories and promote entrepreneurship and micro-enterprises in India .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that rural digitalization technology could fill the void of new institutional theories and promote entrepreneurship and micro-enterprises in India . However, this technology is not sustainable in most developing countries due to inequalities between large and small farmers (Mushi et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%